Public wages in the euro area - towards securing stability and competitiveness - Fédéric Holm-Hadulla; Kishore Kamath; Ana Lamo; Javier J. Pérez; Ludger Schuknecht (European Central Bank (ECB), 2010)
This paper examines the role of government wages in ensuring macroeconomic stability and competitiveness in the euro area. Recent empirical evidence suggests that government wage expenditure is subject to a pro-cyclical bias in most euro area countries and at the euro area aggregate level. Moreover, the evidence points to a strong positive correlation and co-movement between public and private wages in the short to medium term, both directly and indirectly via the price level, in most euro area countries. In a number of countries this interrelation between public and private wages coincided with strong public wage growth and competitiveness losses. These findings underpin the need for prudent public wage policies supported by strong domestic fiscal frameworks and appropriate wage-setting institutions in order to enhance economic stability and competitiveness in Economic and Monetary Union.
Keywords: E22; E50; 330; competitiveness; fiscal cyclicality; government wage expenditure; Vergütungssystem im öffentlichen Dienst; Öffentliche Ausgaben; Erwerbstätigkeit; Lohnniveau; Wettbewerb; Eurozone; EU-Staaten